Biochemcial Changes in Powery Mildew Infected Leaves of Abelmoschus esculentus - Rane, V. P. Pawar and H. E. (Recent Research in Science and Technology, 2011)
Four types of leaf samples A1, A2 , B1 and B2 were taken from healthy and infected plants; and their free amino acids, sugars and organic acid contents were analyzed chromatographically. In case of free amino acids lysine, arginine, asparatic acid, glutamic acid, glycine and phenylatanine were found in all. There was no qualitative difference except for lysine, which gets totally consumed during the course of pathogenesis. Quantitatively was a general increase in amino acid content in B1 sample. In all three sugars were detected, they were fructose, sucrose and raffinose in all the four sample. There was a gradual decrease in the concentration of fructose and sucrose during the pathogenesis. While raffinose was maximum A1 in sample. Organic acid detected in these samples were sebacic acid, adipic acid, succinic acid, maleic acid and citric acid. Succinic acid was totally missing in B2 sample. While adipic and citric acid were maximum in B2 sample. The maximum concentration of sebacic acid was A1 sample and was least in B2. The concentration of maleic acid was maximum in A2 sample.